A Randomized Trial Comparing Seven-Day Ranitidine Bismuth Citrate and Clarithromycin Dual Therapy to Seven-Day Omeprazole, Clarithromycin and Amoxicillin Triple Therapy for the Eradication of Helicobacter pylori. (1st September 2003) - van Zanten, Sander Veldhuyzen; Chiba, Naoki; Barkun, Alan; Fallone, Carlo; Farley, Alain; Cockeram, Alan; Dallaire, Chrystian; Simms, Lorinda; Nicholls, Barbara
Abstract : OBJECTIVE: To assess Helicobacter pylori eradication after one week dual ranitidine bismuth citrate-clarithromycin (RBC-C) or triple omeprazole, clarithromycin and amoxicillin (OCA) therapy. METHODS: In this multicentre Canadian trial, H pylori- positive patients with functional dyspepsia or inactive peptic ulcer disease were randomized to open-label treatment with RBC-C (ranitidine bismuth citrate 400 mg plus clarithromycin 500 mg) or OCA (omezaprole 20 mg, clarithromycin 500 mg and amoxicillin 1000 mg), given twice a day for seven days. Treatment allocation was randomly assigned. H pylori infection was confirmed by positive 13 C-urea breath test ( 13 C-UBT). H pylori status was reassessed by UBT at least four and 12 weeks after treatment (negative: δ 13 CO2 below 3.5 per mil). Intention-to-treat (ITT) eradication rates were determined for all patients with confirmed H pylori infection. Per protocol (PP) rate was determined for all patients treated with at least two evaluable follow-up visits. RESULTS: Three hundred five patients were included in the ITT and 222 in the PP analysis. The ITT eradication rates were 66% for RBC-C and 78% for OCA. The PP success rates were 84% for RBC-C and 96% for OCA. The difference for both ITT 12% (95% CI 2 to 22) and PP 12% (95% CI 4 to 19) were statistically significant, P=0.030 and P=0.007, respectively. Treatment was generally well tolerated. CONCLUSION: The eradication rate for the seven-day dual RBC-C regimen was lower than that for OCA.